Effectiveness of Use of Transcutaneous Electrical Nerve Stimulation (Tens) Modality To Reduce Pain In The Lower Back: Literature Review - Wahyono, Eko; Fikri Ramadhan, Ghozul; Nur Alpiah , Dini (International Journal of Social Research, 2024)
Low back pain (LBP) is a common global health problem that causes disability, increases medical costs, and leads to labor loss. Eighty percent of the population has experienced low back pain at some point in their lives. Chronic low back pain is often associated with comorbidities, significant healthcare costs, and increased use of health services. This study aims to evaluate the effectiveness of Transcutaneous Electrical Nerve Stimulation (TENS) in reducing pain in LBP patients. This study uses a literature review method with strict inclusion and exclusion criteria. The study involved 142 samples, predominantly athletes over 40 years old. The TENS intervention was applied with a frequency of 5 times per week, intensity of 100 Hz, and a duration of 15 minutes for 6 weeks. Pain measurements were conducted using the Visual Analog Scale (VAS) and the Roland Morris Disability Questionnaire (RMQ). The results showed that the intervention group using TENS experienced a significant reduction in pain compared to the control group, with a p-value of <0.001. TENS has proven to be an effective non-invasive therapy method for reducing chronic low back pain. In conclusion, TENS is an effective therapy modality for reducing chronic low back pain and can be used as a non-pharmacological alternative in the management of LBP. Further research is needed to explore the application of TENS in various other clinical conditions.